EP169/#289 Trends in uterine cancer mortality in United States: a 50-year population-based analysis. (4th December 2022) - Lang, Susan; Liao, Cheng-I; Somasegar, Sahana; Johnson, Caitlin; Darcy, Kathleen; Tian, Chunqiao; Kapp, Daniel; Chan, John K
Abstract : Objectives: To analyze mortality trends in uterine cancer in the United States over 50 years. Methods: Mortality data for uterine cancer from 1969–2018 were collected from the National Center for Health Statistics. Mortality rates were extracted using SEER*Stat 8.3.9. Trends (average annual percent change, AAPC) were calculated with Joinpoint 4.9.0.0. Age-adjusted mortality rate was adjusted by the US 2000 standard population. Mortality rates were adjusted by hysterectomy and pregnancy from 2001 to 2018. Results: Uterine cancer mortality decreased from 1969–1997 but increased from 1997–2018. From 2001–2018, mortality rates increased across all age groups after adjusting for hysterectomy and pregnancy. Specifically in 2018, compared to younger patients (50–59 years) the mortality of older (60–69 and 70+ years) was 3x and 7x higher. Mortality rate for non-Hispanic Black (NHB) women was at least 2.2x higher than other races/ethnicities (NHB 17.6/100, 000; non-Hispanic White (NHW) 7.82/100, 000; Hispanic 6.54/100, 000; non-Hispanic Asian/Pacific Islander 4.24/100, 000). Current AAPC in NHB women shows greater annual change than some prior reports (1.87%). Intersection analysis of age and race in the over 60 age group shows NHB women had 3x higher mortality than NHW (72 vs 24/100, 000). Notably, young NHB and Hispanic women (30–39 years) had a higher increase in mortality at 3.3% and 3.8% annually compared to 2.2% in NHW women. Conclusions: Uterine cancer mortality has increased from 1997 to 2018. Older NHBs had the highest mortality rates, and mortality is increasing rapidly in younger minorities. Further studies of molecular, social, and environmental factors are needed to explain and reduce these trends and disparities.